History of wellness, massage and reflexotherapy - Urtnowska-Joppek, Katarzyna; Gajc, Alicja; Goździeniak, Małgorzata (Journal of Education, Health and Sport, 2019)
Biological regeneration, known as wellness is a wide department that has a considerable tradition. Since the ancient times, the beneficial effects of biological regeneration treatments on the human body have been known. The treatments, that offer Spas and wellness centers support people with different medical conditions, but also those who want to experience deep relaxation. Treatments often used in this type of centers are massage and reflexotherapy. Reflexology is an old field of science and therapy, but still not very popular in European countries. Reflexotherapy is designed trigger is a self-healing process and body regeneration. This action is possible by stimulating points and zones on the skin of the face, hands or feet, Which Causes a reflex reaction of internal organs and systems, and a cyclechain of biochemical processes That Their Own trigger processes of stimulation and regeneration of the body.By the activities of spa and wellness center, patient has opportunity to take care of his body's health and additionall a rise of the level of his psychophysical health. All activities Proposed by the biological regeneration strive for body regeneration and it is Mobilize the patient habituate healthy lifestyle habits.